(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Tuberculosis of larynx is a rare form of tuberculosis. Patients usually present with hoarseness of voice or dysphagia and other non- specifi c constitutional symptoms like fever or localized pain. We are reporting a case of 55 year old male who presented to us with hoarseness of voice, odynophagia and a proliferative growth in the epiglottis which was diagnosed as laryngeal tuberculosis on histopathological examination (HPE). He also had associated pulmonary tuberculosis. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5891 SAARCTB 2011; 8(1): 41-43